Real-space condensation in a dilute Bose gas at low temperature: Статьи, посвященные столетию со дня рождения Л. В. Шубникова - Kulik, I. O. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2001)
We show with a direct numerical analysis that a dilute Bose gas in an external potential - which is choosen for simplicity as a radial parabolic well - undergoes at certain temperature Tc a phasetransition to a state supporting macroscopic fraction of particles at the origin of the phase space (r=0,p=0). Quantization of particle motion in a well wipes out sharp transition but supports a distribution of radial particle density r(r) peacked at r=0 (a real-space condensate) as well as the phase-space Wigner distribution density W(r, p) peaked at r=0 and p=0 below the crossover temperature Tc* of order of Tc. Fixed-particle-number canonical ensemble which is a combination of the fixed-N condensatepart and the fixed-m excitation part is suggested to resolve the difficulty of large fluctuation of the particle number (dN~N) in the Bose-Einstein condensation problem treated within the orthodox grandcanonical ensemble formalism.